Capacity in motion: comparative COVID-19 governance in India and South Africa - Chatterji, Tathagata; Götz, Graeme; Harrison, Philip; Moore, Rob; Roy Souvanic (Routledge, 2022)
With the COVID-19 pandemic, critical questions have surfaced in several countries regarding the capacity of the state to respond with agility to the crisis, and to use the crisis in a transformational way over the longer term. These questions are addressed in a comparative study of the State of Kerala in India and the Province of Gauteng in South Africa. The study contributes to two partial gaps in the literature: (1) inadequate attention to the subnational dimensions of crisis governance; and (2) the temporal dimension of state capacity, noting historical and contextual factors conditioning capacity, with shifts through the course of a crisis and beyond. While both territories showed significant agility in response to the crisis, Kerala strengthened its capacities in a way that Gauteng did not, and this had significant implications for the abilities of these governments to both manage the pandemic and leverage the pandemic for longer term benefit.
Keywords: state capacity || subnational || comparative study|| adaptive governance || pandemic governance || COVID-19